Ecotourism in Russian Karelia: Emergence, development, opportunities - Alexander Osipov (Matkailututkimus, 2019)
This review article examines the development of ecotourism in national parks in the Republic of Karelia over the last 30 years. In Russia, the term “ecotourism” has appeared in newspapers and scholarly articles since the 1990s and its popularity is still increasing. The authorities in the Republic of Karelia have argued that tourism and especially ecotourism have the potential to become a major sector of the Republic’s economy. This article focuses on the meaning of this term internationally, and especially in the context of Russia and Karelia, and considers this definition through the lens of conventional historiography. The key issue of this research is the triangular relationship between ecotourists, local communities and wildlife conservation areas or national parks, where ecotourism functions as a major tool, connecting all these points. This paper applies comparative historical research methods as part of a qualitative approach, analysing a variety of primary sources including archive materials, interviews and forum discussions. The article concludes that the slow growth of ecotourism, despite the attempts of regional authorities and the assistance of the European Union, is due to several reasons including remote locations, poor infrastructure and the lack of symbolic meaning for national parks.